(3QSGdI aj GdfSH GdaGWej GdYdhjs - (3Ydj Hf YjSi Hf Ydj GdTQja GdYdejs
(3ChdgG (B:s
(3bO hbY GdNhV eY HYV GdENhGf ai eSCdI , hgj GdfSH gd gh bWYi Ch Xfi s
(3BNQgG (B:s
(3hgj GdebjS KGHJI HGdfSHI Edi GdCe hgj aGWeI QVi Gddg YfgG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B203 s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B(56(3O(B) s
Keywords: (3GdJGQjNs